2011
DOI: 10.1089/aid.2010.0174
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Full-LengthpolGene from Korean Hemophiliacs and Plasma Donors Infected with Korean Subclade B of HIV Type 1

Abstract: There was an outbreak of HIV-1 transmission among 20 out of 122 Korean hemophiliacs from 1990. We assessed the genetic relationships among HIV-1 viruses found in three cash-paid plasma donors whose preseroconversion plasma was used to produce Korean-made clotting factor, 20 hemophiliacs infected with HIV-1 in Korea, three hemophiliacs infected with HIV-1 from clotting factor manufactured outside Korea, and 71 local control patients infected with the Korean subclade of HIV-1 subtype B (KSB). Full-length pol gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(86 citation statements)
references
References 27 publications
6
78
0
2
Order By: Relevance
“…11,12 The use of plasma donors complements the findings of previous studies that lacked plasma donor O sequences. 14 It is suspected that viruses from donors O and P contributed to HIV-1 infections in HPs in Korea.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…11,12 The use of plasma donors complements the findings of previous studies that lacked plasma donor O sequences. 14 It is suspected that viruses from donors O and P contributed to HIV-1 infections in HPs in Korea.…”
Section: Introductionsupporting
confidence: 65%
“…10 Recently, we used a similar method to determine the genetic relatedness of the pol and vif genes between plasma donors and hemophiliacs (HPs). 11,12 These studies showed that pol and vif gene analyses are more suitable in cases with significant time lags between primary infection and sampling because these gene regions evolve more slowly than env and are subjected to less individual patient-specific selection pressures. On September 29, 2011, the Supreme Court of Korea ruled that Company X was responsible for the infection with HIV-1 of Korean HPs B after reviewing our studies on pol and vif genes (Case no.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analyses were also utilized for epidemiologic evaluation of HIV-infected Korean hemophilia patients [6869], and investigation of HIV-1-transmitted drug resistance (TDR) in Korea [6468707172]. Studies on TDR revealed that the drug resistance mutation was not common among treatment-naïve HIV-infected individuals in Korea, and there was little evidence to suggest that TDR in Korea is related to the clonal spread of drug-resistant strains.…”
Section: Phylogenetic Studies Among Korean Hiv-infected Individualsmentioning
confidence: 99%